A Novel Live Attenuated Vaccine Candidate Protects Against Heterologous Senecavirus A Challenge - Sharma, Bishwas; Fernandes, Maureen H. V.; de Lima, Marcelo; Joshi, Lok R.; Lawson, Steve; Diel, Diego G. (Frontiers in Immunology, 2019)
Senecavirus A (SVA) is an emerging picornavirus causing vesicular disease (VD) clinically indistinguishable from foot-and-mouth disease (FMD) in pigs. Notably, there are no vaccines currently available for SVA. Here we developed a recombinant SVA strain (rSVAm SacII) using reverse genetics and assessed its immunogenicity and protective efficacy in pigs. In vivo characterization of the rSVAm SacII strain demonstrated that the virus is attenuated, as evidenced by absence of lesions, decreased viremia and virus shedding in inoculated animals. Notably, while attenuated, rSVA mSacII virus retained its immunogenicity as high neutralizing antibody (NA) responses were detected in inoculated animals. To assess the immunogenicity and protective efficacy of rSVA mSacII, four-week-old piglets were sham-immunized or immunized with inactivated or live rSVA mSacII virus-based formulations. A single immunization with live rSVA mSacII virus via the intramuscular (IM) and intranasal (IN) routes resulted in robust NA responses with antibodies being detected around days 3-7 pi. Neutralizing antibody responses in animals immunized with the inactivated virus via the IM route were delayed and only detected after a booster on day 21 pi. Immunization with live virus resulted in recall T cell proliferation (CD4+, CD8+ and CD4+/CD8+ T cells), demonstrating efficient stimulation of cellular immunity. Notably, a single dose of the live attenuated vaccine candidate resulted in protection against heterologous SVA challenge, as demonstrated by absence of overt disease and reduced viremia, virus shedding and viral load in tissues. The live attenuated vaccine candidate developed here represents a promising alternative to prevent and control SVA in swine.